10 - L’artisanat africain entre domination et résistance de la période coloniale à nos jours : le cas de la ville de Maroua au Nord du Cameroun - François Wassouni, (Afrika Zamani, 2022)
This article attempts to approach the history of domination and resistance in Africa through the arts, particularly through artisanship. It deals with Cameroon, specifically with the main city of Maroua in the northernmost part of the country. In fact, nineteenth century artisanship, practiced in this city by the Kanuri and Hausa, underwent multiple influences from the colo- nial period till today. Other determining factors in the technical, organizational and commercial changes in Maroua’s artisanship involved the support policy implemented by the French colonialists towards the arts, the openness of North Cameroon towards tourism in the 1970’s and the emergence of non governmental organizations working for the promotion of artisanship. Maroua artisans resisted in many ways against all these forms of domination and succeeded, therefore, to safeguard their local know-how which constitutes an important aspect of the history of Cameroon and that of Africa in general.